2020
DOI: 10.1021/acs.joc.0c00608
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of a Bacteriochlorophyll Model Compound Containing trans-Dialkyl Substituents in Ring D

Abstract: Challenges to the de novo synthesis of bacteriochlorophyll a (BChl a ), the chief pigment for anoxygenic bacterial photosynthesis, include creating the macrocycle along with the trans-dialkyl substituents in both pyrroline rings (B and D). A known route to a model bacteriochlorophyll with a gem-dimethyl group in each pyrroline ring has been probed for utility in the synthesis of BChl a by preparation of a hybrid macrocycle (BC-1), which contains a trans-dialkyl group in ring D and a gem-dimethyl group in ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 67 publications
(185 reference statements)
2
29
0
Order By: Relevance
“…The coupling constant values are consistent with the trans configuration of the vicinal protons. 9,11,55 Moreover, 2D NOESY spectroscopy of 26 showed a correlation between the 3-proton and the 2aprotons (first methylene of the propanol substituent), and the 3-methyl and the 2-proton without observing a correlation between the 2-and the 3-protons (see Scheme 9 for numbering). For 28-Br, a correlation was observed between the 3-and 2a-/2b-protons (first/second methylenes of the propanol substituent), but not between the 2-and 3-protons of 28-Br (Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The coupling constant values are consistent with the trans configuration of the vicinal protons. 9,11,55 Moreover, 2D NOESY spectroscopy of 26 showed a correlation between the 3-proton and the 2aprotons (first methylene of the propanol substituent), and the 3-methyl and the 2-proton without observing a correlation between the 2-and the 3-protons (see Scheme 9 for numbering). For 28-Br, a correlation was observed between the 3-and 2a-/2b-protons (first/second methylenes of the propanol substituent), but not between the 2-and 3-protons of 28-Br (Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A current objective is to adapt the general synthesis to accommodate the substituents characteristic of the native macrocycles. To date, we have synthesized the ring C pyrrole, 8 shown that stereodefined model substituents (17-methyl, 18-ethyl) in ring D can be incorporated at an early stage of the synthesis and carried through Knoevenagel and double-ring closure processes to form the macrocycle without loss of stereochemical integrity, 9 refined the conditions for the double-ring closure, 10 compounds containing a 3-acetyl as well as other substituents. 11 The prior incorporation of an acetyl 11 or carboethoxy 9,10 group at the 3-position in each case required independent synthesis beginning with the corresponding substituted pyrrole.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations